GRANITIZATION OF ROCKS IN THE ARCHEAN COMPLEX PENETRATED BY THE KOLA SUPERDEEP BOREHOLE: THE AGE AND SOURCES OF MATTER - Vetrin V.P.; Gorokhovskii B.V. (My University, 2002)
Granitization of rocks in the Archean complex penetrated by the Kola Superdeep Borehole is manifested in the development of nebular, patchy, and unclearly banded migmatites with an age of 2.2 Ga. The amounts of migmatitic material increase from 20-30% in rocks at the deepest levels of the borehole to 50-60% in the tonalitic gneisses in the upper portion of the succession. Analogous migmatites and granitic rocks exposed at the surface and dated at 2.15 Ga occur as a stripe more than 20 km long and 2-6 km wide along the northeastern margin of Pechenga. Compared with the gneisses, the migmatites are richer in rare and volatile components, particularly in Rb, Ba, Nb, Zr, REE, Pb, Cu, Cr, Ni, Co, V, F, P, and CO2. The isotopic composition of the common Pb suggests that this element in feldspars from the migmatized rocks contains a mantle component. The granitization processes were supposedly maintained by fluids that segregated from the chamber of melts parental for the subalkaline volcanic rocks of the Kuetsjarvi unit of the Pechenga Complex. Fluid flows, which percolated from the crystallizing magma toward the chamber roof, migmatized the upper crustal rocks through the precipitation of certain major and trace elements from the fluids (because of a decrease in the solubility of these components with decreasing temperature and pressure). Dating of the migmatized rocks recovered from the lower levels of the borehole and sampled in the Pechenga framing indicates that the granitization processes lasted 50-70 m.y.
Keywords: Archean; Archean; Precambrian::Archean; Precambrian::Archean; Докембрий::Архей; Докембрий::Архей